Peran Orang Tua dalam Pembentukan Nilai-Nilai Agama pada Anak Usia Dini - Al Khusyairi, M. Khoir; Fuaddi, Husni (Journal of Sustainable Education, 2024)
This research was carried out to determine the role of parents in the formation of religious values ​​in early childhood. The method used in this research is qualitative research, where qualitative research as a scientific method is often used and carried out by a group of researchers in the field of social sciences, including educational sciences. Primary data is data taken directly from primary sources, both individuals and legal entities who are competent in their field. Secondary data is data obtained or collected by researchers from various existing sources (researchers as second hand) (Husni Fuaddi, et al, 2023). Secondary data is collected from books, seminar papers, scientific journals and the internet related to the problems studied. The technique for collecting data is by conducting a literature review. The data sources in this study consist of two, namely primary data and secondary data. Primary data is data related to the title of this research, while secondary data is supporting data for the title of this research. The data analysis used in this research is qualitative analysis. The data that has been obtained is then arranged systematically. by using an inductive thinking method, namely drawing conclusions and problems that are general in nature and then drawing them into conclusions that are specific in nature. The results of the research are that the role of parents in the formation of religious values ​​in early childhood includes the family as the foundation for religious and socio-cultural education, a place to foster feelings of affection and a place to learn.